Efecto del encalado y diferentes niveles de sombra sobre la productividad de Theobroma cacao L. clon CCN51, en la provincia de Zamora Chinchipe, - Quezada Jumbo, Jonathan Andrés (2023)
The cultivation of cocoa (Theobroma cacao L.) is of great socioeconomic importance in Latin America and the Caribbean as it is one of the main export products, either as raw material or processed; cocoa cultivation generates significant sources of economic income and provides work for thousands of people, contributing 5% of the national economically active population (EAP) and 15% of the rural EAP, however, the acid soils of this region limit the availability and absorption of nutrients. Therefore, in this study, the effect of liming and different levels of shade on the productivity of Theobroma cacao L. clone CCN51, in the province of Zamora Chinchipe, was evaluated. A completely randomized design with a bifactorial arrangement (shade and liming) was established, with 4 treatments and 4 replications. Canopy diameter, fruit length, number of fruits/plant, estimated yield, fruit weight, electrical conductivity and soil pH, SPAD index and leaf area index were evaluated. The effect of the treatments on the variables was evaluated by ANOVA and Tukey's test (p<0.05). The results showed that significant differences were found between treatments in the variables crown diameter and SPAD index; the crown diameter increased with shade. However, there was no significant effect for the other variables evaluated. The results of this study show that shade is not essential for cocoa plants during the cocoa production stage, while liming did have an effect on soil pH and therefore increased the availability of nutrients. Key words: Theobroma cacao L, growth, yield, shade, liming.